A utilização do valor econômico adicionado como ferramenta de gestão financeira - Dutra Junior, Dalton Jacinto (2001)
Lets imagine how should be fine to disclose a new measure form to investigate the businessman performance as if the job done is bringing back to the stockholder, the best results. Also, would be better to exists an executive compensation, by his add value created to the stockholder.The word ¿add value¿ is at the summit point on the financial world, all the companies are involved on creating add value' into the assets.So, the EVA (Economic Value Added) has come, a patented trade mark by a consulting corporation company, the Stern & Stewart Co. as a new indicator of companies performances.This assignment has motivated to running out na empirical research in order to find out the right methodology its qualitys and its differentials.'